Affect and cognition in criminal decision making - Van Gelder, Jean-Louis.; Elffers, H.; Nagin, Daniel (London : Routledge/Taylor & Francis Group, 2014)
'Since its publication in 1986, Cornish & Clarke's seminal work The Reasoning Criminal: Rational Choice Perspectives on Offending has become a very influential text in criminal decision making theory. However, Criminology seems to have lost contact with developments in other disciplines in decision making, especially with modern socio-psychological theory such as the'Dual Process Model of Decision Making'.This book questions the extent to which criminal decision making theory should take on board recent socio-psychological results. It provides a conceptual analysis of the role of affect and cognition in criminal decision making and considers the possibility of incorporating effect within the rational choice model, as opposed to using the dual process model. In two conceptual and ten empirical chapters it is carefully argued which role emotions can and should play in decision making. Affects such as anger, shame, and sexual arousal are discussed. The empirical studies use a wide variety of methods from interviews and observations to experiments and questionnaires, and treat crimes so diverse as street robbery, pilfering, and sex offences. It will be of interest to criminologists, social psychologists, judgment and decision making (JDM) researchers, behavioral economists and sociologists alike'--
'Since its publication in 1986, Cornish & Clarke's seminal work The Reasoning Criminal: Rational Choice Perspectives on Offending has become a very influential text in criminal decision making theory. However, Criminology seems to have lost contact with developments in other disciplines in decision making, especially with modern socio-psychological theory such as the'Dual Process Model of Decision Making'. This book questions the extent to which criminal decision making theory should take on board recent socio-psychological results. It provides a conceptual analysis of the role of affect and cognition in criminal decision making and considers the possibility of incorporating effect within the rational choice model, as opposed to using the dual process model. In two conceptual and ten empirical chapters it is carefully argued which role emotions can and should play in decision making. Affects such as anger, shame, and sexual arousal are discussed. The empirical studies use a wide variety of methods from interviews and observations to experiments and questionnaires, and treat crimes so diverse as street robbery, pilfering, and sex offences. It will be of interest to criminologists, social psychologists, judgment and decision making (JDM) researchers, behavioral economists and sociologists alike'--
Includes bibliographical references and index.
Keywords: Criminal psychology; Decision making; Choice (Psychology).; Criminology